DEKONSTRUKSI KARAKTER DRUPADI DALAM PEWAYANGAN (STUDI GENDER DAN LIVING QUR’AN MENGENAI POLIANDRI) - Ahmad Hidayatullah; Syamsul Bakhri (Jurnal Sosiologi Reflektif, 2021)
One of the many evidences about the concepts of justice and gender equality in Islam can be seen in the creation of the plot and of a central female character in the Javanese puppet, namely Drupadi. This article employs a qualitative research with this literature study approach to determine the deconstruction character of Drupadi.  The validity of the data is obtained by triangulating data sources and integrating data from journals and books about Drupadi characters in puppets, supported by analysis of gender studies and living Qur'an studies of the concept of polyandry. The results showed that there is a deconstruction of the character of Drupadi figures from the Hindu to the Islamic version. Drupadi, who is described in the Mahabharata story of having five husbands, in a Javanese puppet show, especially after the arrival of Islam, is described only married to Yudhistira. The deconstruction of Drupadi's character as a symbol of women is no longer objectified. Drupadi's new character reflects equality between men and women in Islam.Satu dari sekian bukti tentang adanya konsep keadilan dan kesetaraan gender dalam Islam bisa dilihat dalam pembangunan alur dan karakter tokoh perempuan sentral pada pewayangan Jawa, yakni Drupadi. Penelitian kualitatif dengan pendekatan studi pustaka ini, bertujuan untuk menentukan dekonstruksi karakter Drupadi di Wayang. Validitas data diperoleh dengan melakukan triangulasi sumber data, mengintegrasikan data dari jurnal dan buku tentang karakter Drupadi dalam wayang dengan berfokus pada analisis studi gender dan Living Qur’an mengenai poliandri. Hasil penelitian menunjukkan bahwa telah terjadi dekonstruksi karakter tokoh Drupadi dari versi Hindu ke versi Islam; Drupadi dalam cerita Mahabharata melakukan Poliandri dengan 5 suami, dalam pewayangan Jawa setelah datangnya Islam hanya bersuamikan Yudhistira. Dekonstruksi karakter Drupadi menjadi simbol bahwa perempuan tidak lagi menjadi objektifikasi seksual. Karakter Drupadi yang baru mencerminkan kesetaraan antara pria dan perempuan dalam ajaran Islam.